Educational leadership in the future through Finnish principals’ perspective - Ryu, Seonjeong (2020)
The study aims to examine the future educational leadership from the perspective of Finnish principals. The study established two research questions: 1) What kind of leadership practices do Finnish school principals use to prepare future education?; 2) How do Finnish school principals describe the future of educational leadership? This study was approached as a qualitative method of a case study. The method of data collection was conducted through interviews with three principals in Finland, and the results were inductively derived through the content analysis method. All three principals in Finland have at least seven years of principal experience. Finnish principals were expressing leadership in a variety of ways to prepare for the future. They tried to ensure basic well-being conditions for students, teachers, and principals. They expressed their leadership to draw cooperation from teachers as well as students. Besides, they actively encouraged new attempts and challenges and took a tolerant attitude. The Finnish principals selected Dual leadership, Teacher leadership, and Participative leadership as future leadership styles. These three leaderships are implied by shared leadership. The study found that Finnish school principals are trying to stick to the basics rather than trying something new to prepare for the future. They emphasized the importance of education preventing dropouts, basic competency education, and lifelong learning. In this study, educational leaders who are preparing for the future are given a message that they need to consider the steadfastness of the basic things that they have done well rather than the desire for new things.